PENGARUH CUSTOMER PERCEIVED VALUE TERHADAP REPURCHASE INTENTION DALAM GAME GENSHIN IMPACT - Egar Surya; Anang Muftiadi; Arianis Chan (JURNAL LENTERA BISNIS, 2024)
The present study seeks to examine the extent to which customer perceived value influences repurchase intention among consumers of in-game purchase products in the Genshin Impact game, with a case study conducted on members of the Genshin Impact Official Indonesia group. The research approach employed is quantitative, utilizing a descriptive verification method. The sampling technique involves non-probability sampling, specifically purposive sampling. Data were collected through questionnaires, observations, interviews, and literature studies. The data analysis was performed using simple linear regression, a significance test (T-test), and the coefficient of determination (r2). The study population consists of consumers of in-game purchase products in the Genshin Impact game, with a sample size of 120 respondents. The results indicate a significant influence of customer perceived value on repurchase intention among consumers of in-game purchase products in the Genshin Impact game. This implies that the higher the perceived customer perceived value, the greater the repurchase intention exhibited by consumers of in-game purchase products in the Genshin Impact game. Keywords: Customer Perceived Value, Repurchase Intention, Online Games